2002
DOI: 10.1002/mus.10245
|View full text |Cite
|
Sign up to set email alerts
|

Within‐train neuromuscular propagation varies with torque in paralyzed human muscle

Abstract: Electromyographic (EMG) recordings may serve an important role in predicting torque during repetitive activation of paralyzed muscle. We compared the initial M-wave to the subsequent M-waves of the same train under fatigued and recovered conditions in the paralyzed human soleus muscle. Sixteen individuals with chronic (n = 13) or acute paralysis (n = 3) had the tibial nerve activated before and after a repetitive supramaximal stimulation protocol. The mean within-train M-wave amplitude and median frequency inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…It should be noted that the current study did not disclaim the influence of peripheral fatigue on patients with MS. Lenman et al suggested that patients with MS suffered from higher levels of peripheral fatigue than nondisabled subjects [5]. A previous study showed that in paralyzed muscle, twitch potentiated more in low frequency fatigue status than in fresh status [32]. Although they did not reach statistical significance, the results of the current study showed that the twitch force potentiated before decreasing (Figure 2(c)), suggesting that the subjects might have been in a peripheral fatigue status before the voluntary fatigue protocol was applied.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the current study did not disclaim the influence of peripheral fatigue on patients with MS. Lenman et al suggested that patients with MS suffered from higher levels of peripheral fatigue than nondisabled subjects [5]. A previous study showed that in paralyzed muscle, twitch potentiated more in low frequency fatigue status than in fresh status [32]. Although they did not reach statistical significance, the results of the current study showed that the twitch force potentiated before decreasing (Figure 2(c)), suggesting that the subjects might have been in a peripheral fatigue status before the voluntary fatigue protocol was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the exact mechanism, this finding has important practical implications for functional electrical stimulation (FES) in patient populations. Although there are potential benefits from low-frequency FES in the upper limb after spinal cord injury, the benefits do not occur in all patients, due to an inability to achieve high muscle power and due to fatigue of any evoked forces (7,20). Because the long-pulse-width, high-frequency stimulation trains elicit the enhanced forces via afferent mediated stimulation of motoneurons, they have the advantage of potentially activating the motoneurons according to the size principle (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…One may argue that the amplitude of M waves should be reduced after ES due to fatigue. However, previous research reported that the reduction of M waves after fatigue was related to neuromuscular transmission failure and that they recovered within 5 min after fatigue [45,46]. In this study, the M wave was measured at 10 min post-treatment, at which time the neuromuscular transmission should have been fully recovered.…”
Section: Discussionmentioning
confidence: 93%